Self-assembled microtissues loaded with osteogenic MSCs for in vivo bone regeneration - Li, Hui; He, Zihao; Li, Wenjing; Li, Jiao Jiao; Lin, Jianhao; Xing, Dan (Frontiers in Bioengineering and Biotechnology, 2022)
Bone regeneration strategies based on mesenchymal stem cell (MSC) therapy have received widespread attention. Although MSC incorporation into bone scaffolds can help with the repair process, a large number of studies demonstrate variable effects of MSCs with some noting that the inclusion of MSCs does not provide better outcomes compared to unseeded scaffolds. This may in part be related to low cell survival following implantation and/or limited ability to continue with osteogenic differentiation for pre-differentiated cells. In this study, we incorporated MSCs into gelatin microcryogels to form microtissues, and subjected these microtissues to osteogenic induction. We then mixed as-formed microtissues with those subjected to 6 days of osteogenic induction in different ratios, and investigated their ability to induce in vitro and in vivo osteogenesis during self-assembly. Using a full-thickness rat calvarial defect model, we found that undifferentiated and osteogenically induced microtissues mixed in a ratio of 2:1 produced the best outcomes of bone regeneration. This provides a new, customizable cell-based therapeutic strategy for in vivo repair of bone defects.